Implementasi Project Based Learning dalam Pembeajaran Seni Rupa untuk Meningkatkan Kreativitas Siswa Jurusan Animasi di SMK Negeri 2 Palu - Alifia Syahnina Rizqi; Iriaji Iriaji (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model in art education as an effort to enhance the creativity and artistic understanding of Animation Department students at SMK Negeri 2 Palu. The study employed a descriptive qualitative approach involving animation students and supervising teachers as research subjects. Data were collected through observation, documentation, and reflective analysis during the teaching assistance program. The learning implementation was carried out through the introduction of traditional, modern, and contemporary art concepts integrated with practice-based creative project activities. The findings indicate that the application of PjBL significantly increased students’ active engagement in the learning process, strengthened their conceptual understanding of visual arts, and improved their ability to express creative ideas through visual works. Furthermore, the establishment of the “Kreasi Animasi Seni Budaya” community provided a collaborative space that supported the sustainable development of students’ creativity and artistic reflection. These findings demonstrate that project-based art learning is effective in optimizing the artistic competencies.